Typification of names in Camellia (Theaceae), II - Zhao, Dongwei; Parnell, John A.n.; Hodkinson, Trevor R. (Phytotaxa, 2018)
Following our previous work of typifying names of Camellia Linnaeus (1753: 698) (Zhao et al. 2017), three more names of this genus are lectotypified here.